Arte pubblica e rigenerazione urbana: il caso del quartiere Aurora a Torino - Mela, Sara (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2021)
Many studies have addressed the delicate relationship between art and gentrification, sometimes emphasizing the role played by artists in creating an attractive context for the workers of the new creative class, other times assigning them a certain responsibility in producing gentrification effects. This article aims at understanding whether and how the work of artists can contribute to the regeneration of the suburbs without producing gentrification effects. While any action aimed at improving public space can run the risk of producing gentrification effects, for some interventions the risk seems more significant. Empirical investigation has been carried out through a campaign of interviews with privileged witnesses in the Aurora neighborhood in the northern suburbs of Turin, bringing to light a variety of initiatives that move with the aim of bringing attention to the suburbs without producing gentrification: small-scale projects with a temporary nature, carried out together with the inhabitants, careful to places, focused on immaterial aspects (building relationships, giving voice, bringing new energy, spreading creativity, etc.). At the same time, also the effects produced in terms of regeneration seem limited: the experiences seem to be disconnected one from each other, giving the image of artistic bubbles, struggling to find a common direction and coordinated working methods. Artists themselves move solitarily, without finding the right support in public institutions, which struggle to embrace the innovative scope of these experimentations within a more general framework of a political project. An important issue is therefore the need for institutions to be able to engage with initiatives that have arisen spontaneously, ensuring impact on a broader scale, while at the same time enhancing their innovative scope: offering public institutions ideas for a different use of the city.